DETERMINAN PENGAMBILAN KEPUTUSAN DALAM PERENCANAAN PERSALINAN PADA KELAS IBU HAMIL - Fatimah Fatimah Fatimah; Sugeng Triyani Triyani; Aisyah Aisyah Aisyah (Poltekkes Kemenkes Jakarta III, 2015)
Class of pregnant women means a group of pregnant women those learn about health of pregnant together. The members attend several meeting with midwifery to improve their knowledge and skills telated pregnancy topics, including childbirth, postpartum care, newborn care, myths, infectious diseases and birth certificates. In short, the class discusses and shares experiences among pregnant women and to health workers about the health of mother and child (Kesehatan Ibu dan Anak: KIA) themes. This study group activity called